The lipooligosaccharide of the gut symbiont Akkermansia muciniphila exhibits a remarkable structure and TLR signaling capacity - Pilar Garcia-Vello; Hanne L. P. Tytgat; Janneke Elzinga; Matthias Van Hul; Hubert Plovier; Marta Tiemblo-Martin; Patrice D. Cani; Simone Nicolardi; Marco Fragai; Cristina De Castro; Flaviana Di Lorenzo; Alba Silipo; et al. (Nature Communications, 2024)
Abstract The cell-envelope of Gram-negative bacteria contains endotoxic lipopolysaccharides (LPS) that are recognized by the innate immune system via Toll-Like Receptors (TLRs). The intestinal mucosal symbiont Akkermansia muciniphila is known to confer beneficial effects on the host and has a Gram-negative architecture. Here we show that A. muciniphila LPS lacks the O-polysaccharide repeating unit, with the resulting lipooligosaccharide (LOS) having unprecedented structural and signaling properties. The LOS consists of a complex glycan chain bearing two distinct undeca- and hexadecasaccharide units each containing three 2-keto-3-deoxy-D-manno-octulosonic acid (Kdo) residues. The lipid A moiety appears as a mixture of differently phosphorylated and acylated species and carries either linear or branched acyl moieties. Peritoneal injection of the LOS in mice increased higher gene expression of liver TLR2 than TLR4 (100-fold) and induced high IL-10 gene expression. A. muciniphila LOS was found to signal both through TLR4 and TLR2, whereas lipid A only induced TLR2 in a human cell line. We propose that the unique structure of the A. muciniphila LOS allows interaction with TLR2, thus generating an anti-inflammatory response as to compensate for the canonical inflammatory signaling associated with LOS and TLR4, rationalizing its beneficial host interaction.